Efficacy and Safety of Regorafenib Combined with Toripalimab in the Third-Line and beyond Treatment of Advanced Colorectal Cancer. (24th September 2021) - Yu, Wei; Tao, Qiaomeng; Zhang, Yufeng; Yi, Fengming; Feng, Long
Abstract : Background . The most effective treatment of immune checkpoint inhibitors (ICIs) is restricted in microsatellite instability (MSI-H) subsets of advanced colorectal cancer, but MSI-H only accounts for 4-5% among them. ICIs are completely ineffective in advanced colorectal cancer patients with microsatellite stable (MSS), according to literatures published. Regorafenib is a novel tyrosine kinase inhibitor (TKIs) that could normalize tumor blood vessels by inhibiting vascular endothelial growth factor receptor and its downstream, thus improving cytotoxic T cell infiltration in tumor microenvironment, which has a synergistic effect with ICIs. Toripalimab is a type of anti-PD-1 monoclonal antibody produced by Junshi Biosciences in China. Herein, we aimed to explore the efficacy and safety of regorafenib combined with toripalimab in the third-line and beyond treatment of advanced colorectal cancer. Methods . We evaluated the outcomes of MSS patients with advanced colorectal cancer who received regorafenib combined with toripalimab in the Second Affiliated Hospital of Nanchang University from June 2019 to January 2021. These patients had previously received at least second-line treatment; the regimens were oxaliplatin and irinotecan-based chemotherapy and/or accompanied with bevacizumab or cetuximab. Thirty-three patients were treated orally with regorafenib 80 mg or 120 mg once daily for 21 days, 28 days as a cycle, combined with intravenous toripalimab until disease progression or intolerant to adverse reactions. We used the Kaplan–Meier method to estimate the rate of progression-free survival (PFS) and log-rank method to do a statistical test of the survival curve. The Cox regression model was used to analyze the influence of multiple factors on PFS. The primary endpoints were objective remission rate (ORR) and disease control rate (DCR). The secondary endpoints were the incidence of adverse reactions and median progression-free survival (mPFS). Results. The evaluation of treatment effects was assessed according to RECIST 1.1. Four patients (12.12%) got partial response, twelve patients (36.36%) experienced stable disease, and seventeen patients (51.52%) suffered progressive disease. ORR was 12.12% and DCR was 48.48%. mPFS was 113 days (95% CI: 0–272.1). In univariate analysis, patients who had previously received second-line treatment were significantly better than those who had received third-line or more treatment (p = 0.005 ). Lung metastasis was a negative factor in combined therapy (p = 0.032 ). Five patients without previous treatment of bevacizumab were effective. Previous treatment without bevacizumab showed a trend of effective when combination therapy (p = 0.034 ). It was also a positive factor that the Eastern Cooperative Oncology Group performance status (ECOG) score was 0 (p = 0.034 ). Multivariable Cox regression analysis showed the number of previous chemotherapy lines and excision of primary lesions were independent prognostic factors. The most common treatment-related adverse reactions were hand-foot syndrome (33.33%), liver dysfunction (27.27), hypothyroidism (24.24%), fever (24.24%), fatigue (21.21%), leukopenia (15.15%), hypertension (12.12%), platelet count decreased (6.06%), diarrhea (3.03%), and myocarditis (3.03%); one patient stopped treatment as myocarditis. The incidence of grade 3/4 adverse reactions was 9.09%. Conclusions . Regorafenib combined with toripalimab has a promising effect in the third-line and beyond treatment of advanced colorectal cancer. In the early use of combination therapy, excision of primary lesions can have a positive impact in regorafenib and toripalimab combination. This treatment-related adverse reactions are tolerant in combined therapy.